General Self-Efficacy of Nurses in Clinical Activity - Butkutė, Karina; Sabaliauskas, Stanislav (Slauga. Mokslas ir praktika, 2025)
A high level of nurses’ general self-efficacy is a crucial factor in ensuring the quality and safety of healthcare. Nurses’ self-efficacy abilities help effectively manage stress and anxiety, reduce the risk of burnout, and improve their professional efficiency. Nurses often face heavy workloads, challenges, technological changes, and experience emotional strain, making their self-efficacy levels dependent on the work environment. High self-efficacy is associated with greater job satisfaction and better mental health. Although self-efficacy is linked to psychological well-being and professional effectiveness, the factors influencing nurses’ self-efficacy have not yet been sufficiently explored. The aim of this study is to review and present the latest literature data on nurses’ general self-efficacy in clinical practice. The methods employed are a systematic literature review which was conducted using the PubMed, Web of Science, and Scopus databases, searching for articles analysing issues related to nurses’ general self-efficacy in clinical activity. Results and conclusions. Twelve articles were selected for the systematic literature review. The analysis of the literature showed that nurses’ self-efficacy directly correlates with lower levels of stress, anxiety, and burnout. Half of the selected publications revealed that nurses’ self-efficacy is above the average level. The researched studies demonstrated that personality traits, work environment, and organizational support significantly influence self-efficacy, which is associated with greater job satisfaction, self-esteem, and professional resilience. A decline in self-efficacy can significantly deteriorate nurses’ psychological well-being.